2019
DOI: 10.3906/sag-1808-114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sarcopenia, sarcopenic obesity, and phase angle in geriatric gastrointestinal cancer patients: before and after chemotherapy

Abstract: Background/aim: The purpose of this study was to determine sarcopenia, sarcopenic obesity and phase angle (PA) and the influence of chemotherapy (CT) on anthropometric measurements and and the PA in in geriatric patients with gastrointestinal (GI) cancer. Material and methods: The anthropometric measurements, calf circumference (CC), upper midarm circumference (UMAC), and hand grip strength (HGS), have been measured to understand muscle function of 153 patients (mean age of 70.5 ± 5.6 years, 28.8% female, 71.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In patients with metastatic urothelial carcinoma and colorectal carcinoma, BIA was deemed comparable to axial L3 CT scan imaging in estimating sarcopenia . BIA had high correlation with calf circumference and grip strength in patients with gastrointestinal neoplasia . BIA overestimated muscle mass when compared with DXA scan in patients with lung cancer .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In patients with metastatic urothelial carcinoma and colorectal carcinoma, BIA was deemed comparable to axial L3 CT scan imaging in estimating sarcopenia . BIA had high correlation with calf circumference and grip strength in patients with gastrointestinal neoplasia . BIA overestimated muscle mass when compared with DXA scan in patients with lung cancer .…”
Section: Resultsmentioning
confidence: 85%
“…For articles that remained after the initial screen, 65 full texts were reviewed for eligibility. Ultimately, 24 studies were selected for inclusion in the systematic review—18 articles and 6 abstracts —with a total of 3,607 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of muscle mass with CT is well defined and established (Cruz‐Jentoft, 2019). In various cancer types, sarcopenia has become a hot topic, as a prognostic marker and related with survival (Gokyer, 2019; Hopanci Bicakli, 2019; Ozawa, 2019). However, there is still to be learned from other various imaging modalities including metabolic imaging, FDG PET.…”
Section: Discussionmentioning
confidence: 99%
“…Survival was reported to be related with sarcopenia in patients with cancer, since survival is a measure of paramount interest in studies of all types of cancer (Gokyer, 2019; Hopanci bicakli, 2019; Nakamura, 2015, 2019; Ozawa, 2019). In our study, we observed a relation with sarcopenia and survival both in terms of CT‐based and FDG‐based metabolic evaluation, which suggested the utility of metabolic evaluation in muscle assessment in MM.…”
Section: Discussionmentioning
confidence: 99%